Effective MAC scheme for improving usable throughput in WLAN - FENG Hui; WANG Ting; HU Bo (Tongxin xuebao)
In DCF mode of 802.11 infrastructure BSS, the usable throughput was compromiseel by two main factors. One was the channel utilization ratio decreases when the number of competing stations increases. The other one was the se- vere asymmetry between downlink and uplink data because AP possesses no advantage position when accessing the share channel. Both problems were solved by a new MAC scheme which adjusts the minimum contention window of AP and station to optimized values derived from a mathematical model under downlink/uplink bandwidth control. Meanwhile, a new estimation method for station number is proposed via dynamic MAC addresses statistic at AP side.